COPPADIS‐2015 (COhort of Patients with PArkinson's DIsease in Spain, 2015): an ongoing global Parkinson's disease project about disease progression with more than 1000 subjects included. Results from the baseline evaluation. (4th July 2019) - Santos García, D.; Jesús, S.; Aguilar, M.; Planellas, L. L.; García Caldentey, J.; Caballol, N.; Legarda, I.; Hernández Vara, J.; Cabo, I.; López Manzanares, L.; González Aramburu, I.; Ávila Rivera, M. A.; et al.
Abstract : Background and purpose: In Parkinson's disease (PD), the course of the disorder is highly variable between patients. Well‐designed, prospective studies for identifying PD progression biomarkers are necessary. Our aim was to show the results of baseline evaluations of an ongoing global PD project, COPPADIS‐2015 (Cohort of Patients with PArkinson's DIsease in Spain, 2015). Methods: This was an observational, descriptive, nationwide study (Spain). The recruitment period ended in October 2017. Baseline evaluation included more than 15 validated scales and complementary studies in a subgroup of participants. Results: In total, 1174 subjects from 35 centres were considered valid for baseline analysis: 694 patients (62.6 ± 8.9 years old, 60.3% males), 273 caregivers (58.5 ± 11.9 years old, 31.8% males) and 207 controls (61 ± 8.3 years old, 49.5% males). The mean disease duration was 5.5 ± 4.4 years. Hoehn and Yahr stage was 1 or 2 in 90.7% of the patients whilst 33.9% and 18.1% of them presented motor fluctuations and dyskinesias, respectively. The mean Non‐Motor Symptoms Scale total score was 45.4 ± 38.1, and 30.4% of the patients presented cognitive impairment, 16.1% major depression, 12.7% impulse control disorder, 7.2% compulsive behaviour, 57.2% pain and 13.2% falls. Compared to the control group, PD patients presented a significantly higher burden of non‐motor symptoms and a worse quality of life. More than 300 subjects conducted complementary studies (serum biomarkers, genetic and neuroimaging). Conclusions: Parkinson's disease is a complex disorder and different non‐motor symptoms are frequently present and are more prevalent than in controls. In real clinical practice it is important to ask for them.